Doxorubicin loaded polylactide nanoparticles functionalized histamine promote apoptosis of human gastric cancer cells AGS - Patrycja Jaroniek; Marek Brzeziński; Magdalena Chmiela; Weronika Gonciarz (Scientific Reports)
Abstract Gastric cancer is a dominating cause of cancer-related deaths in the world. The modern perspective in gastric cancer treatment is the application of nanoparticles (NPs) affecting the growth of cancer cells to increase the effectiveness of anti-tumor therapy. The use of advanced nanosystems that deliver anti-cancer drugs and biologically active substances may strongly rely on the expression of cancer-associated targets. The aim of this study was to examine the synergistic effect of doxorubicin (DOX) and histamine (His) in NPs DOX-loaded composed of poly(lactic) acid -PLA with histamine end groups (NPs-His-DOX) towards human gastric cancer cells (AGS) in vitro in conjunction with increasing oxidative stress, DNA damage, and cell apoptosis, as well as diminishing cell proliferation. The influence of studied NPs on the expression of intracellular adhesion molecule (ICAM)-1, which may facilitate the cytotoxic reaction of lymphocytes against gastric cancer cells, has also been determined. We showed a significant (p < 0.05) synergistic effect of His and DOX in the NPs His-DOX in increasing oxidative stress as demonstrated by an increased level of 4-hydroxynonenal (4HNE), DNA damage, cell apoptosis, in conjunction with a significant (p < 0.05) inhibition of cell proliferation as well as the disintegration of the cell monolayer. Furthermore, NPs His-DOX upregulated a cell deposition of ICAM-1. This study shows that NPs His-DOX facilitates the delivery of the anticancer drug DOX into the milieu of cancer cells, which results in increased cell death. Furthermore, upregulation of ICAM-1 on gastric cancer cells may increase anti-tumor cytotoxic activity of immunocompetent cells.